Factors associated with treatment for latent tuberculosis in persons living with HIV/AIDS - Daniela Silva de Aquino; Líbia Cristina Rocha Vilela Moura; Magda Maruza; Adriana Paula da Silva; Ricardo Arraes de Alencar Ximenes; Heloísa Ramos Lacerda; Demócrito de Barros Miranda Filho; Maria de Fátima Pessoa Militão de Albuquerque (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract The aim was to identify factors associated with non-initiation of prophylactic treatment of latent tuberculosis infection (LTBi) in persons living with HIV/AIDS (PLWA), based on a prospective cohort study of PLWA ≥ 18 years of age in two referral services for HIV/AIDS. Of the 232 patients eligible for treatment of LTBi, 69.8% initiated treatment. Following multivariate logistic regression analysis, only treatment in one of the two referral services was associated with non-initiation of treatment for LTBi (p < 0.001). TB incidence in the cohort was 0.6/100 person-years. TB incidence in patients that initiated treatment of LTBi was 0.4/100 person-years, compared to 1.2/100 person-years in those that did not initiate treatment, but the difference was not statistically significant. The study's most interesting finding was that the main factor associated with the likelihood of treatment for LTBi was the health service where the patient was treated.